Crisis communication strategies during the code red phase of aviation industry and media framing discrepancies: case of Malaysia Airlines twin tragedy / Muhammad Hafizuddin Fakhrullah Zakaria, Nurliyana Yusnaidi and Zulkifli Abd. Latif - Zakaria, Muhammad Hafizuddin Fakhrullah; Yusnaidi, Nurliyana; Abd. Latiff, Zulkifli (Centre For Media And Information Warfare Studies, 2021)
The aviation industry was deemed to be most vulnerable when it comes to crises in the transportation industry.) This vulnerability is mainly due to the risks of corporate bankruptcy and deaths in the worst-case scenario as airlines are majorly exposed to every type of crises such as financial, terrorism, financial, management failures, and natural factors [1]. Thus, in order to address such crises, it is important for MAS to have a proper and effective crisis communication approach. This study will be looking into 1) the crisis communication strategies and procedures adapted by Malaysia Airlines and 2) The discrepancies of media framing to the actual event situation. This qualitative study utilizes the case study approach where the perspective and insights are gained through an in-depth interview with an expert who was personally involved and in charge of the crisis communication during when the Emergency Operation Committee (EOC) took over the crisis management of MH370 and MH17. A thematic analysis and constant comparison with open-source data strategy will be carried out upon the data gathered and themes are extracted in fulfilling the aim of the study. The findings for RO1 shows the procedure during crisis response and the crisis response strategies during the pre-crisis, crisis / code red, and post crisis phase. For RO2 the finding shows discrepancies in the alleged delayed response from Malaysia Airlines as well as in the existence of assumptions that lead to conspiracy theories and fake news.